ความเชื่อมั่นของประชาชนต่อการดำเนินงานของมหาวิทยาลัยขอนแก่น: Public Confidence in the Performance of Khon Kaen University. - สิริภานุวัฒน์ วรวิทย์ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This study examined public confidence in the performance of Khon Kaen University across demographic factors including gender, age, education level, occupation, and monthly income. Quantitative research design was employed using concepts related to public confidence and institutional operations, and related studies. Data were collected using questionnaires from 494 residents aged 18 and above living in Khon Kaen Municipality during the 2024 fiscal year. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, and inferential statistics using one-way ANOVA with LSD post hoc comparisons. The findings indicated that most respondents were female, aged 45–60, held a bachelor’s degree, were self-employed, and earned 5,000–10,000 baht per month. Primarily received university news through public relations signs, community leaders, and community radio, while Facebook was the most frequently used online platform, followed by YouTube and the university website. Overall public confidence in the university was high, particularly in academic and healthcare services, followed by graduate production, research and innovation, organizational quality development, personnel and management, and arts and culture preservation. Higher confidence levels were observed among working women and diverse gender groups aged 35–60 with higher education and stable occupations, likely due to greater access to university information and services. Conversely, younger individuals, those with lower education levels, and people in less secure occupations reported lower confidence. Although income was not a major determinant, higher-income groups occasionally demonstrated significantly stronger confidence. The findings indicate that Khon Kaen University play a significant role in fostering public trust through academic and healthcare services, which received the highest level of trust, reflecting their accessibility and tangible benefits to the community. Confidence in graduate production, research and innovation, and organizational development also remained high; however, community-oriented research outcomes and public awareness still require further improvement. In addition, public confidence is influenced by service experiences and social structures. Therefore, strengthening communication policies, proactive services, and promoting research outcomes to the community are essential for enhancing public engagement and supporting sustainable institutional development.